2002
DOI: 10.1175/1520-0493(2002)130<1493:ecocsd>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Characteristics of Convective Systems during TRMM-LBA

Abstract: In this paper, data collected from 51 days of continual upper atmospheric soundings and TOGA radar at ABRACOS Hill during the TRMM-LBA experiment are used to describe the mean thermodynamic and kinematic airmass properties of wet season convection over Rondonia, Brazil. Distinct multi-day easterly and westerly lower tropospheric wind regimes occurred during the campaing with contrasting airmass characteristics. Westerly wind periods featured modest CAPE (1000 J kg-1), moist conditions (>90% RH) extending throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 19 publications
6
76
1
4
Order By: Relevance
“…The lack of early-morning convection may also reflect the over-prediction of PBL stratocumulus simulated by the model at night above cold ground. Halverson et al (2002) reported that low-and mid-level humidity show substantial variation between the different wind regimes. This finding is important in terms of the formation of stratiform rain, cloud cover, and thermal instability during the regimes.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of early-morning convection may also reflect the over-prediction of PBL stratocumulus simulated by the model at night above cold ground. Halverson et al (2002) reported that low-and mid-level humidity show substantial variation between the different wind regimes. This finding is important in terms of the formation of stratiform rain, cloud cover, and thermal instability during the regimes.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In both wind regimes, maximum precipitation occurs during the early afternoon, although the peak on EWR days is slightly later than that on WWR days. Halverson et al (2002) used radar and local sounding-network data at the Abracos site to study the thermodynamics and kinematics of air mass properties during the two wind regimes. They found that on EWR days, rainfall is higher and convective precipitation makes a greater contribution to the daily total.…”
Section: Introductionmentioning
confidence: 99%
“…Variability in microphysical structure is commonly observed as a function of meteorological forcing. For example, in the Amazon basin easterly low-level winds typically result in convection that is more continental in character, whereas westerly flow results in a more maritime structure Halverson et al 2002;Petersen et al 2002;Rickenbach et al 2002;Silva Dias et al 2002). Another example is in northern Australia, with ''monsoon'' versus ''break'' convection taking on characteristics of the maritime versus continental archetypes, respectively Williams et al 1992;Randell et al 1994;May and Ballinger 2007;May et al 2008).…”
Section: Introduction a Backgroundmentioning
confidence: 99%
“…In the ER, convection typically occurs in high convective available potential energy (CAPE) and vertical shear environments and is more vertically developed and electrified compared to the WR (Cifelli et al 2002;Halverson et al 2002;Petersen et al 2002).…”
Section: Introductionmentioning
confidence: 99%